Effect of Gestational Weight Gain on Associations Between Maternal Thyroid Hormones and Birth Outcomes - Zhou, Bin; Chen, Yao; Cai, Wen-Qian; Liu, Ling; Hu, Xi-Jiang (Frontiers in Endocrinology, 2020)
Purpose: The aim was to investigate the associations between maternal thyroid parameters within the normal ranges during early pregnancy and birth outcomes, and further to examine whether the associations were modified by gestational weight gain (GWG). Methods: Maternal serum thyroid-stimulating hormone (TSH), free thyroxine (FT4), and free triiodothyronine (FT3) concentrations within the normal ranges during early pregnancy were measured from 8107 pregnant women in Wuhan, China. The associations between maternal thyroid parameters and birth outcomes (birth weight, birth length, and low birth weight) were analyzed using multivariable adjusted regression models, and effect modification by pre-pregnancy body mass index (BMI) category and GWG were further evaluated. Results: Maternal TSH and FT4 concentrations were negatively associated with birth weight, and the latter only occurred in normal weigh women with inadequate and excessive GWG, as well as in both underweight and overweight women with excessive GWG (e.g., β= -359.33g, 95%CI:-700.95, -17.72 in underweight women with excessive GWG for per unit increase of FT4 concentrations). Moreover, maternal FT4 and FT3 concentrations were associated with increased risk for low birth weight, and the latter only occurred in normal weigh women with inadequate GWG (OR=2.52, 95%CI: 1.00, 6.36 for per unit increase of FT3 concentrations). These associations still persist when maternal thyroid parameters were modeled as quintiles. Main conclusion: Maternal normal thyroid function during early pregnancy with excessive and inadequate GWG may adversely influence fetal growth.